HUBUNGAN KEMAMPUAN MOTORIK SISWA DENGAN HASIL BELAJAR PENJASKES DI SDN 50/VI LUBUK MENTILIN KECAMATAN JANGKAT - Hadi, Metral; Ismi Mori Saputra, Deka (Jurnal Muara Olahraga, 2024)
ABSTRACT This research begins with learning outcomes which are influenced by two factors, namely internal factors and external factors. The low quality of physical education learning outcomes can be concluded from the low motor skills of students. The lower a person's motor skills, the lower the learning outcomes. This research is correlational research, namely research to determine the level of relationship between the independent variable and the dependent variable. The sample used in this research was 32 student at SDN 50/VI Lubuk Mentilin, Jangkat district. The results of this research are that there is a relationship between students' motor skills and physical education learning outcomes at SDN 50/VI Lubuk Mentilin, Jangkat District. This is indicated by the research results obtained, namely tcount = 3.802 > ttable = 2.042, with a value of r = 0.570, r2 = 0.324, the contribution is 32.4%. Keywords: Motor Skills, learning outcomes.